Impact of voluntary termination of pregnancy on female sexual function: A french monocentric longitudinal study - Léa Rouchou; Dounia Baïta; Sophie Regueme; Claude Hocke (PLoS ONE, 2026)
Background Voluntary termination of pregnancy (VTOP) is common in France, yet its impact on female sexual function remains incompletely understood. Previous studies often reported changes in Female Sexual Function Index (FSFI) scores without validated diagnostic thresholds, limiting clinical interpretation. This study aimed to assess the prevalence and evolution of sexual dysfunction over six months following VTOP, and to explore factors associated with persistent dysfunction using a validated FSFI threshold. Methods We conducted a prospective, longitudinal study enrolling 186 adult women undergoing VTOP at Bordeaux University Hospital (Feb–May 2023). Sexual dysfunction was assessed at inclusion and at 1, 3, and 6 months post-VTOP using the validated FSFI (dysfunction defined as score ≤26.55). Additional medical and socio-demographic data were collected via self-administered questionnaires. Logistic mixed-effects models evaluated time effects and factors associated with dysfunction. The primary outcome was the prevalence of sexual dysfunction over time. Results Among participants completing follow-up (n = 47 at 6 months), sexual dysfunction prevalence decreased from 61.3% at baseline to 36.2% at 6 months (aOR = 0.17; 95% CI, 0.09–0.29). Median FSFI scores increased from 24.7 to 28.5 (p = 0.012), particularly in desire, arousal, and orgasm domains. Being single (aOR = 2.17; 95% CI, 1.09–4.34) and reporting psychological symptoms were independently associated with persistent dysfunction. Discussion Among women completing follow-up, sexual function appeared to improve over six months following pregnancy resolution. Integrating psychological and relational support into post-VTOP care may help optimize recovery. The high attrition and monocentric design limit generalizability and warrant cautious interpretation.